Y=cos3x
y=1/x
y=ln5x
y=(2+3x)^5(do potęgi)
y=x+5 pierw.x
y=ctgpierw.x
y=tg8x^3
y=2^tgx
y=sin(5x+4)
y=4x^3pierw.x
y=(3x^3-14x^2-x+25)^4
y=cos^3x
y=tg^4*2x
y=x+1/pierw. 1-x
y=xpierw.x^2 +1
y=arctg 1+x/1-x
y=(sinx)^cosx
y=ln3x
y=5*10^3x
y=sin^2*x-cos^2*x
y-2cos^2*x/2
y=arcsin(log x/10)
y=ln(tgx/2)-cosx*ln(tgx)
y=(sinx)^tgx

1

Odpowiedzi

2009-10-23T12:35:33+02:00
Podejrzewam że trzeba obliczyć pochodne?
Zatem

a)y=cos3x
y'= (cos3x)*3=-3sin3x

b)y=1/x
y'=-1/x²

c)y=ln5x
y'=(ln5x)*5=5*1/x=5/x
d)y=(2+3x)^5(do potęgi)
y'=(2+3x)^5)'= 5(2+3x)⁴*3=15(2+3x)⁴
e)y=x+5 pierw.x
y'=(x+5√x)'=1+5*1/2√x=1+5/2√x
f)y=ctgpierw.x
y'=(ctg√x)=-1/sin²√x*1/2√x=-1/2sin²√x*√x
g)y=tg8x^3
y'=(tg8x³)=1/cos²8x³*3*8x²=1/cos²8x³*24x²
h)y=2^tgx
y'=(2^tgx)'=2tgx*x^(tgx-1)
i)y=sin(5x+4)
y'= cos(5x+4)*5=5cos(5x+4)
j)y=4x^3pierw.x
y'=(4x^3√x)'=3√x*4x^(3√x-1)
k)y=(3x^3-14x^2-x+25)^4
y"=4(3*3x²-14*2x-1)³=4(9x²-28x-1)³
l)y=cos^3x
y'=3x(-sin^3x)cos^(3x-1)
ł) y=tg^4*2x
y'=4*2tg^2x^tg³2x
k)y=x+1/pierw. 1-x
y'= (x+1)'(√1-x)-(x+1)*(√x-1)'/(√1-x)²=
(√1-x)-(x+1)*(1/2√x-1)/(1-x)
m)y=xpierw.x^2 +1
y' = (x√x²+1)'=(x)'*(√x²+1)+x*(√x²+1)'=
(√x²+1)+x*(1/2√x²+1)*2x=
[(√x²+1)²+2x²]/√x²+1=
[3x²+1]/√x²+1
n)y=arctg 1+x/1-x
y'= 0+(x'*(1-x)-x*(1-x)')/(1-x)²= (1-x+x)/(1-x)²=1/(1-x)²
o)y=(sinx)^cosx
cosx*sinx^(cosx-1)
p)y=ln3x
y'= 1/x*3=3/x
r)y=5*10^3x
y'= 5*10^3x*ln10
1 5 1